Güney Paphlagonia’da Roma ve Erken Bizans Dönemine Ait Bazı Arkeolojik Bulgular: Üçbölük Köyü - Yıldırım, Yaşar Serkal; Gür, Durmuş (Journal of History Culture and Art Research, 2019)
Some Archaeological Findings from Roman and Early Byzantine Period in Southern Paphlagonia: Üçbölük Village Abstract Karabuk is located in the Northwestern Black Sea and surrounded by Zonguldak to the west, the Black Sea to the north, Kastamonu to the east, Cankırı to the south. Ucboluk (Ilbarit) Village that located 20 km southeast of Safranbolu district of Karabuk, is a historic settlement founded on the slopes of Soganli Valley. Within the scope of the scientific project “Surveys in Roman and Byzantine Periods of Karabuk Province and its Districts”, which started for the first time in 2017, research has been carried out in Safranbolu and surrounding settlements. Through this study, finding the rock-cut tomb, altar and wine presses, columns, double columns, column headings, inscriptions dated to Roman and Early Byzantine Periods and many archaeological data around Ucboluk (Ilbarıt) Village in Soganli Valley were examined and recorded. Archeological artifacts found in Ucboluk Village, which included in the borders of the region called Paphlagonia in history, shed light on the historical, architectural and socio-economic structure of the area from the Roman and Early Byzantine Periods. Ucboluk village and surrounding areas, which attracted the attention of many researchers and travellers since the 19th century such as Leonhard (1915), Gökoğlu (1952), Belke (1996), Dökü (2008), Laflı and Christof (2009, 2012), were examined in detail by us with together archaeological and art history experts for the first time in 2017. When evaluation on historical data of Ucboluk Village, having abundant water resources, which located on the southern slope of the Soganli Valley is considered to be an intensive agricultural activity based on wine production in the region. The finding vine branches and agricultural tools on the rock-cut tombs and grave stalks and especially rock-cut wine presses in Ucboluk (Ilbarıt) and around it, are indicative of this. Within the scope of this paper, the rock-cut tombs previously found and the rock-cut wine presses, rock-cut altar, cross sacred rock structure and architectural plastic artifacts that were first detected by us in Ucboluk village, which is one of the rural settlements in southern Paphlagonia, are evaluated in general perspective. Also, under the light of those finding artifacts, the architecture, the religious and social economic structure of the rural settlements in the region during the Roman and Early Byzantine periods were tried to be identified. Öz Kuzeybatı Karadeniz’de yer alan Karabük; batıdan Zonguldak, kuzeyden Karadeniz, doğudan Kastamonu, güneyden ise Çankırı ile çevrilidir. Karabük’ün ilçesi Safranbolu’nun yaklaşık 20 km güneydoğusunda bulunan Üçbölük (Ilbarıt) Köyü, Soğanlı Vadisi’nin yamaçlarında kurulmuş tarihi bir yerleşim alanıdır. İlk olarak 2017 yılında başladığımız “Karabük İli ve İlçeleri Roma ve Bizans Dönemi Yüzey Araştırması” adlı bilimsel proje kapsamında Safranbolu ve çevresindeki yerleşim alanlarında araştırmalar gerçekleştirilmiştir. Araştırmalarımız kapsamında Soğanlı Vadisi’nde bulunan Üçbölük (Ilbarıt) Köyü çevresindeki Roma ve Erken Bizans Dönemi'ne tarihlendirilen kaya mezarı, kaya altarı, şarap işliği, sütun, çifte sütun, sütun başlığı, stel, yazıt ve pek çok arkeolojik veri incelenerek kayıt altına alınmıştır. Tarihte Paphlagonia olarak adlandırılan bölgenin sınırları içine dahil olan Üçbölük Köyü’nde tespit edilen arkeolojik eserler Roma ve Erken Bizans Dönemi tarihçesi başta olmak üzere bölgenin mimari ve sosyo-ekonomik yapısına ışık tutmaktadır. 19. yüzyıldan itibaren Leonhard (1915), Gökoğlu (1952), Belke (1996), Dökü (2008), Laflı ve Christof (2009, 2012) gibi birçok araştırmacı ve seyyahın dikkatini çeken Üçbölük Köyü ile çevresindeki yerleşim alanları ilk defa 2017 yılında tarafımızca, arkeoloji ve sanat tarihi uzmanları eşliğinde detaylı bir şekilde incelenmiştir. Zengin su kaynaklarına sahip Soğanlı Vadisi’nin güney yamacı üzerinde yer alan Üçbölük Köyü, tarihi verileri kapsamında değerlendirildiğinde yörede şarap üretimine dayalı yoğun bir tarımsal faaliyet olduğu belirlenmiştir. İşlikler başta olmak üzere Üçbölük Köyü ve çevresinde tespit edilen steller ve kaya mezarları üzerinde yer alan asma dalları ile tarım aletleri bunun göstergesidir. Bu bildiri kapsamında Güney Paphlagonia’da kırsal yerleşim alanlarından biri olan Üçbölük’te daha öncesinde tespit edilmiş olan kaya mezarları ve ilk defa tarafımızdan tespit edilen şarap işliği, kaya altarı vb. mimari plastik eserler hakkında elde edilen bulgular genel bir bakış açısı ile değerlendirilmiş ve Roma ve Erken Bizans Dönemi’nde bölgedeki kırsal yerleşim alanlarının mimarisi, dini ve sosyo-ekonomik yapısı anlaşılmaya çalışılmıştır.